Believing in Karma: The Effect of Mortality Salience on Excessive Consumption - Chen, Siyun; Wei, Haiying; Meng, Lu; Ran, Yaxuan (Frontiers in Psychology, 2019)
This research proposes that mortality salience leads individuals to engage in differentiation of excessive consumption based on their appraisal of the karmic system. Study 1 demonstrated that mortality salience interacts with belief in karma to jointly determine excessive consumption, such that consumers faced with mortality salience tend to increase overconsumption likelihood when they have a weak (vs. strong) belief in karma. Study 2 revealed the underlying mechanism – temporal perspective – that drives our main effect. Replicating the findings of the two previous studies, study 3 further delineated interest frame as a theoretically derived boundary condition for the proposed interaction effect on excessiveness. Theoretical and, practical implications, as well as avenues for future research are discussed.